Mixed‐method research protocol: defining and operationalizing patient‐related complexity of nursing care in acute care hospitals. (20th December 2016) - Huber, Evelyn; Kleinknecht‐Dolf, Michael; Müller, Marianne; Kugler, Christiane; Spirig, Rebecca
Abstract: Aim: To define the concept of patient‐related complexity of nursing care in acute care hospitals and to operationalize it in a questionnaire. Background: The concept of patient‐related complexity of nursing care in acute care hospitals has not been conclusively defined in the literature. The operationalization in a corresponding questionnaire is necessary, given the increased significance of the topic, due to shortened lengths of stay and increased patient morbidity. Design: Hybrid model of concept development and embedded mixed‐methods design. Methods: The theoretical phase of the hybrid model involved a literature review and the development of a working definition. In the fieldwork phase of 2015 and 2016, an embedded mixed‐methods design was applied with complexity assessments of all patients at five Swiss hospitals using our newly operationalized questionnaire 'Complexity of Nursing Care' over 1 month. These data will be analysed with structural equation modelling. Twelve qualitative case studies will be embedded. They will be analysed using a structured process of constructing case studies and content analysis. In the final analytic phase, the quantitative and qualitative data will be merged and added to the results of the theoretical phase for a common interpretation. Cantonal Ethics Committee Zurich judged the research programme as unproblematic in December 2014 and May 2015. Discussion: Following the phases of the hybrid model and using an embedded mixed‐methods design can reach an in‐depth understanding of patient‐related complexity of nursing care in acute care hospitals, a final version of the questionnaire and an acknowledged definition of the concept.